(3CSfi GdeWGdH aj UdI GdCbGQHs - (3CMeO Hf eMeO Hf Ydj Hf nMnLQ GdngrjnJej GdSYOj GdCfUGQj, TgGH GdOjf TjN GdESdGe, CHh GdYHGS,J (B974 (3g` s
(3ChdgG (B:s
(3Gddge dGSgd EdG eG LYdJg SgdkG, CfJ LYdJ GdMRf SgdkG s
(3BNQgG (B:s
(3hSGFQ GdQhGFM GdWjHI gPG BNQ eG hLOfGg ef gPG GdcJGH hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B234 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B152s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B81s
Keywords: (3GdJUha hGdBOGH GdTQYjIs